The plot- thematic classifi cation historical novels by J. Zeydan (Journal of Oriental Studies, 2016)
The article attempts to plot and thematic classifi cation of historical novels J.Zeydan. Of the nineteen historical novels J.Zeydan twonovels were devoted to events in the late XYIII century and the fi rst half of XIX century, and the remaining seventeen novels refl ect theevents of the Middle Ages reproduced in chronological order cycles.